Efek Media Massa dalam Pembentukan Opini Publik di Masa Pandemi Covid-19 - Tatang Sudrajat; Leni Rohida (Prosiding, 2022)
In the current situation of the COVID-19 pandemic, the mass media have an influence on information about all things about the pandemic, from the status of the new variant to the impact of this pandemic. The mass media are fully responsible for all information presented to the public, so that the public will feel comfortable and at ease with the information presented by the mass media. One of the roles of the mass media is to educate and increase public awareness. Because from the beginning the mass media followed the developments of the COVID-19 pandemic. An opinion is a statement on a controversial issue. Opinions arise as a result of discussions on controversial issues that give rise to differences of opinion. Mass media as a means of delivering information to the public plays an important role in shaping public opinion. This study uses a documentary approach by observing and analyzing all information related to the object of research. In building a research ojek there are steps that the researcher takes, namely: firstly observing and analyzing various information related to object search. Second, collect various sources related to the object of research so that the phenomenon can be explained. The results of this study are expected to maximize the presence of the media which plays an important role in the context of the COVID-19 pandemic. In addition to carrying out its vital function, the mass media must also be able to provide fresh air through the information presented. No more sensationalism, now is the time for the media to return to presenting information based on relevant facts